Tunneling injection and recombination of carriers in self-assembled quantum dots - Chaggar, Amrik Richard (2009)
This thesis describes an experimental investigation of the resonant injection of carriers into self-assembled indium arsenide (InAs) quantum dots incorporated in the intrinsic region of gallium arsenide (GaAs) p-i-n resonant tunneling diodes, and of the resulting electroluminescence spectrum associated with carrier recombination in the quantum dots, wetting layer and GaAs matrix.